Spatial and temporal cladoceran community responses to environmental change and anthropogenic impacts in southwestern Québec. Issue 3 (1st October 2016) - Cooper, Emily; Neil, Karen; Gajewski, Konrad
ABSTRACT: A high-resolution sediment record from Lac Brûlé, southwestern Québec, was studied to determine the effects of long-term climate change and anthropogenic impacts on cladoceran assemblages of the late Holocene. Temporal shifts in cladoceran communities were closely associated with known century-scale climatic episodes, namely the Medieval Warm Period (750–1250 CE), the Little Ice Age (1450–1850 CE) and the twentieth-century warming. Forward selection indicated the importance of catchment variables and aquatic primary production in governing cladoceran communities. This suggests that higher trophic levels in Lac Brûlé were responsive to changes in the physical and chemical properties of the lake, perhaps as an indirect consequence of climatic change. The exploitation of the Wallingford-Back Mine in the immediate watershed of Lac Brûlé from 1924 to 1972 CE also had notable impacts on cladoceran assemblages. To strengthen interpretations of the Lac Brûlé record, relationships between cladoceran assemblages and limnological variables were studied in surface samples from 31 lakes from the surrounding region. This spatial analysis identified nutrients (phosphorus and nitrogen) and pH as the most influential variables driving changes in present-day cladoceran communities. However, the performance of cladocera-based inference models was insufficient to quantitatively reconstruct variables in the down-core analysis of Lac Brûlé.